IMPROVING STUDENTS™ ACHIEVEMENT IN READING COMPREHENSION THROUGH THINK PAIR SHARE STRATEGY - Handayani, Umami - (TRANSFORM: Journal of English Language Teaching and Learning, 2014)
ABSTRACT This research is designed to improve the students™ reading comprehension in English through Think Pair Share strategy. the objective of the research is to develop Think Pair Share to improve the students™ reading comprehension. The research was  conducted by using  classroom action research. The finding showed that Think Pair Share strategy was successful in improving students™ reading comprehension. The improvement couls be seen from the increase of students™ reading scores. Besides, the finding also showed that Think Pair Share strategy was effective in enhancing the students™ participation, especially in term of sharing ideas, asking and answering questions. Keyword: Think Pair Share strategy, improve, reading comprehension